Functional Convergence of Thalamic and Intrinsic Projections to Cortical Layers 4 and 6 - Lee, C.C.; Imaizumi, K. (Нейрофизиология, 2013)
Ascending sensory information is conveyed from the thalamus to layers 4 and 6 of the
sensory cortical areas. Interestingly, receptive field properties of cortical layer-6 neurons
differ from those in layer 4. Do such differences reflect distinct inheritance patterns from
the thalamus, or are they derived instead from local cortical circuits? To distinguish between
these possibilities, we utilized in vitro slice preparations containing the thalamo-cortical
pathways of the auditory and somatosensory systems. Responses from neurons in layers 4
and 6 that resided in the same column were recorded using whole-cell patch clamp. Laserscanning photostimulation via uncaging of glutamate in the thalamus and cortex was used to
map the functional topography of thalamo-cortical and intracortical inputs to each layer. In
addition, we assessed the functional divergence of thalamo-cortical inputs by optical imaging
of flavoprotein autofluorescence. We found that the thalamo-cortical inputs to layers 4 and
6 originated from the same thalamic domain, but the intracortical projections to the same
neurons differed dramatically. Our results suggest that the intracortical projections, rather
than the thalamic inputs, to each layer contribute more to the differences in their receptive
field properties Висхідний потік сенсорної інформації передається з таламуса до шарів 4 та 6 сенсорних кортикальних зон. Цікавим є
те, що властивості рецептивних полів у нейронів кортикального шару 6 є відмінними від таких у шарі 4. Чи відображають дані відмінності специфічні природжені патерни таламічних зв’язків або вони зумовлені специфікою локальних
кортикальних нейронних мереж? Щоб зробити вибір між такими можливостями, ми використали слайсові препарати in vitro, котрі вміщували таламо-кортикальні шляхи слухової
та соматосенсорної систем. Застосовуючи методику петчклемп у конфігурації «ціла клітина», ми відводили відповіді нейронів шарів 4 та 6, розташованих в одній і тій самій
кортикальній колонці. Для отримання карт функціональної
топографії таламо-кортикальних та інтракортикальних входів, до кожного із шарів ми використовували методику лазерної скануючої стимуляції, що забезпечувала вивільнення глутамату в таламусі та корі. Окрім того, ми оцінювали
функціональну дивергенцію таламо-кортикальних входів за
допомогою візуалізації аутофлуоресценції флавопротеїнів.
Було виявлено, що таламо-кортикальні входи до шарів 4 та
6 походили від ідентичних таламічних регіонів, тоді як інтракортикальні проекції до одних і тих самих нейронів значно відрізнялися. Наші результати примушують думати, що
саме інтракортикальні проекції того або іншого шару, а не
таламічні входи в більшій мірі визначають відмінності відповідних рецептивних полів у згаданих шарах.